Effects of an educative program for talent development in female children from Peru’s vulnerable zones - Coronel Capacyachi, Elizabeth Jesús (2020)
The research’s objective was to find out if the TALENTVEFT program has any effect on the development of multiple intelligences in children. The study, of explanatory level, used the experimental method and a quasi-experimental design of longitudinal cut. The sample consisted of 182 students, divided into two groups: the experimental group and the control group. The experimental group participated in 4 one-hour sessions for 4 weeks (one session per week). The control group did not participate in any workshops. Both groups were evaluated before and after (pretest and postest) the intervention with the Armstrong professor’s inventory of multiple intelligences, adapted by Prieto and Ballester (Alvarez, 2014). The results showed statistically significant differences between the two measurement moments at the level of interpersonal intelligence (t = 7,752 / p = ,000) and intrapersonal intelligence (t = 7,416 / p = ,000). This allows us to suggest the effectiveness of the program and to leave the possibility of its replication open, considering also the reliability and validity of its evaluation tools.   DOI: https://doi.org/10.31876/sl.v4i1.42